Economic and business field development at Economic Regional of Pandeglang Regency - Deris Desmawan; Rizal Syaifudin (PT Larva Wijaya Penerbit, 2022)
The economic and business field development at Pandeglang regency is slowly started to replace the superior sector that is called as the agriculture sector. Therefore, it is important for Pandeglang Regency to identify their superior sector which must be suitable for the development and economy growth in the current situation. Although, nowadays the superior sectors at Pandeglang have identified yet and there is no analysis about whether or not the superior sector could push the stability of economic growth. Referring to this case, this research analyzes about the superior sectors at Pandegang Regency which is intended to push the stability of the economic sector, with the mixed method of qualitative and quantitative by the approach of economy basic. The tools of analysis that will be used in this research are shift-share, location quotients, and typology Klassen analysis.